2008
DOI: 10.1038/leu.2008.298
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow transplantation and donor lymphocyte infusion in a mouse model of irradiation-induced myelodysplastic/myeloproliferation syndrome (MD/MPS): evidence for a graft-versus-MD/MPS effect

Abstract: The role of graft-versus-malignancy reactivity in the effects of allogeneic hematopoietic stem cell transplantation and donor lymphocyte infusion (DLI) for myelodysplastic syndromes is as yet not well established. Clinical data are limited and animal models are scarce. Here, we report on the effects of allogeneic bone marrow transplantation (alloBMT) and DLI in a novel model of irradiation-induced murine myelodysplastic/myeloproliferation syndrome (MD/MPS). Total body irradiation with 8.5 Gy in SJL/J mice gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…32 Another long-term study (up to 80 days after irradiation) showed that SJL mice developed a severe wasting syndrome with a higher mortality rate. 33 The authors showed that SJL mice died due to myeloproliferation, leukemic transformation, and infection. Likewise, we observed higher mortality in SJL recipient mice after a longer period of time (up to 60 days) after the irradiation and BMT (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…32 Another long-term study (up to 80 days after irradiation) showed that SJL mice developed a severe wasting syndrome with a higher mortality rate. 33 The authors showed that SJL mice died due to myeloproliferation, leukemic transformation, and infection. Likewise, we observed higher mortality in SJL recipient mice after a longer period of time (up to 60 days) after the irradiation and BMT (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, up to now there is no exact mechanism explaining the regulatory effects of allogeneic NA-BMCs. Although, the irradiation dosage is equivalent to the current protocols used in other transplantation settings [29] , this minimal dosage probably permits survival of significant numbers of endogenous host stem cells that can be activated after transplantation of allogeneic NA-BMCs. It is possible, that the therapeutic benefit of allogeneic NA-BMCs on improved survival can only be observed using this radiation setting.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols to generate radiation chimeras and perform bone marrow transplantation assays have been described previously. 41 Briefly, WT mice and Nix 2 /2 mice were firstly subjected to g-irradiation at a dose of 8.5 Gy from a 60 Co source (Institute of Zoology, Chinese Academy of Sciences), and then the prepared bone marrow cells (5 3 10 6 cells per mice) were injected into the tail vein of the irradiated mice. Four weeks after transplantation, the reconstituted mice were tested to analyze FeCl 3 -induced thrombosis of the carotid artery, tail-bleeding time, and platelet activation as described previously.…”
Section: Radiation Chimeras and Bone Marrow Transplantation Assaymentioning
confidence: 99%